Type of Victimization Exposure, Perpetrator Type, and Timing of Victimization: The Impact on Behavioral Health Outcomes - Kowalski, Melissa A. (Journal of interpersonal violence, 2024)
The effect of abuse victimization in correctional samples has been researched previously, particularly with an eye toward these experiences on justice-involved youth and prison samples’ offending and recidivism behavior. The role of this type of victimization, including physical abuse, sexual abuse, and polyvictimization, is less studied in jail populations. The effect of abuse victimization is also less researched among other outcomes, including behavioral health disorders (BHDs) and substance use disorder (SUD). While the effect of abuse, generally, has been examined, less is known about how abuse perpetrator type and timing of abuse impact justice-involved individuals’ outcomes. Using logistic regressions, we examined the influence of abuse perpetrator type (non-stranger or stranger) and timing (before childhood, after childhood, or before and after childhood) in a population of jailed adults from one state (n = 4,713). Outcomes studied included internalizing BHDs, externalizing BHDs, and severe SUD. Results indicated that abuse perpetrated by a non-stranger yielded a greater impact on mental illness compared to abuse perpetrated by a stranger. In contrast to abuse experienced as an adult, childhood abuse was more consistently associated with internalizing and externalizing disorders but was not related to severe SUD, with an exception of physical abuse. Further, BHDs and SUD were strongly associated with each other. Overall, polyvictimization had the strongest effect on the outcomes compared to either physical abuse or sexual abuse alone. Our findings suggest that screening for abuse experiences as a potential destabilizing factor in justice-involved populations could improve case management and interventions for people incarcerated in jails. Results also highlight the importance of distinguishing between the perpetrator type of abuse and timing of abuse.